Dirāsah ‘An Al-Luṣgah wa Al-Laknah wa Al-Laḥn - Muflihah Muflihah; Muhammad Bashori (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
AbstractThe disadvantages of pronunciation are a special phenomenon with a specific circumstance, and form part of the phenomenon in general and that the ancient Arab linguists referred to the phenomenon of speech defects, and tried to interpret and clarify, and the article was scattered about the disadvantages of pronunciation in multiple sources and the defects that occur in some pronunciation is Lisping and Accent And melody. And Lisping is to equate letters one with other letters or change the letter ra (ر) with  lam( ل)  and sin (س) with sa ( ث) and Accent is the pronunciation of speech or the entry of characters from a language into Arabic and melody is wrong in the expression and language and singing and cotton and exposure and meaning or reverberation of voice and understanding and the meaning of say and drop the expression Language and gesture.Keywords: Lisping , Accent, Melody. دراسة عن اللثغة و اللكنة و اللحنمفلحلة، محمد بصريالجامعة الإسلامية الحكومية سونان أمبيل سوراباياmuflihah@uinsby.ac.id, Serol_seril@yahoo.comملخصعيوب النطق هي ظاهرة خاصة لها ظرفها المعيَّن، وتشكل جزءًا من الظاهرة عامة و إن اللُّغويين العرب قديمًا أشاروا إلى ظاهرة عيوب النطق، وحاوَلوا تفسيرها وتوضيحها، وقد تناثَرتِ المادة التي تناوَلَتْ عُيُوب النطق في مصادرَ متعدِّدةٍ وكانت العيوب التي تحدث في بعض النطق هي اللثغة و اللكنة و اللحن. و اللثغة أن تعدل الحرف إلى غيره او أن يُصَيِّر الراء لامًا والسين ثاءً في كلامه و اللكنة هي العجمة في الكلام او دخول الحروف من لغة أعجمية إلى اللغة العربية و اللحن هو الخطأ في الإعراب واللغة والغناء والقطنة والتعريض والمعنى او ترجيع الصوت والفهم ومعنى القول وإسقاط الإعراب واللغة والإيماء.الكلمات الرئيسية: اللثغة، اللكنة، اللحن